1987
DOI: 10.1152/ajpgi.1987.253.1.g93
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between oxygen radicals and gastric mucin

Abstract: The gastrointestinal epithelium is continuously exposed to reactive oxygen metabolites that are generated within the lumen. In spite of this exposure, the healthy epithelium appears unaffected, suggesting efficient mechanisms for protection against these potentially cytotoxic oxidants. The objective of this study is to characterize the interaction between purified gastric mucin and hydroxyl radicals generated from the interaction between ferric iron and ascorbic acid. We found that both native and pronase-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 0 publications
3
80
0
Order By: Relevance
“…Kim and Byrd [75] have proposed that defects in mucin synthesis or enhanced mucin degradation may be important in the pathophysiology of ulcerative colitis. Grisham and co-workers have recently shown that hydroxyl radical degrades and depolymerizes purified mucin, as measured by decreases in viscosity [76]. Thus, if one considers mucin depletion as the result of increased oxidative stress, perhaps along the biochemical lines studied by Baker and co-workers [77] for the degradation of articular cartilage proteoglycan, the mucin defect theory and the oxygen radical theory become unified.…”
Section: Circumstantial Clinical Evidencementioning
confidence: 98%
“…Kim and Byrd [75] have proposed that defects in mucin synthesis or enhanced mucin degradation may be important in the pathophysiology of ulcerative colitis. Grisham and co-workers have recently shown that hydroxyl radical degrades and depolymerizes purified mucin, as measured by decreases in viscosity [76]. Thus, if one considers mucin depletion as the result of increased oxidative stress, perhaps along the biochemical lines studied by Baker and co-workers [77] for the degradation of articular cartilage proteoglycan, the mucin defect theory and the oxygen radical theory become unified.…”
Section: Circumstantial Clinical Evidencementioning
confidence: 98%
“…Mucus also is known to have antioxidant capabilities (44). The sugar moieties in mucus may act similarly to mannitol and glucose in scavenging hydroxyl radical and H202 (45,46). Mucus glycoproteins react with H202; in the process both H202 and glycoproteins are degraded (44,47,48 (52), increased nonspecific airway reactivity, increased specific airway resistance, increased respiratory frequency on exercise, and an involuntary reduction of maximal inspiratory capacity (53).…”
Section: Nonenzymatic Antioxidant Defensesmentioning
confidence: 99%
“…It is known that gastric mucin interacts with ROS, especially hydroxyl radical in vitro (17). We have reported that teprenone exerts protective and preventive effects against acute gastric mucosal lesions in rats with water immersion restraint stress not only by preservation of gastric mucus synthesis and secretion but also by inhibition of neutrophil infiltration and enhanced lipid peroxidation in the gastric mucosa (13).…”
Section: Introductionmentioning
confidence: 96%